2014
DOI: 10.3892/mmr.2014.3004
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid inhibits the growth of BGC-823 gastric carcinoma cells via a p53-mediated pathway

Abstract: The aim of the present study was to investigate the effects of deoxycholic acid (DCA) on BGC‑823 human gastric carcinoma cells and to explore the possible mechanisms underlying any such effects. Cell proliferation was detected using a 3‑(4,5‑Dimethylthiazol‑2‑yl)‑2,5‑diphenyl tetrazolium bromide assay, cell morphology was observed by inverted microscopy, and cell cycle progression and the mitochondrial membrane potential were analyzed using flow cytometry. The expression of Bcl‑2, Bax, p53, Cyclin D1 and cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…Thus, some studies focused on the role of p53 in mediating cell apoptosis induced by chemotherapeutic agents. 30,32,33 In this study, we found that the level of p53 was significantly increased due to treatment with alantolactone, which further suggested that p53 was a key gene in the apoptosis of BGC 823 and SGC-7901 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, some studies focused on the role of p53 in mediating cell apoptosis induced by chemotherapeutic agents. 30,32,33 In this study, we found that the level of p53 was significantly increased due to treatment with alantolactone, which further suggested that p53 was a key gene in the apoptosis of BGC 823 and SGC-7901 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Yang et al. pointed out that on the one hand, DCA can inhibit the proliferation of gastric carcinoma cells by arresting the cell cycle in the G0/G1 phase, and on the other hand, it can induce apoptosis of gastric carcinoma cells via a p53-mediated pathway ( 52 ). Jang et al.…”
Section: Bile Acids In Cancer Cell Proliferation and Deathmentioning
confidence: 99%
“…In the recent years, potential anticancer properties of NaDCA have gained increasing attention because of at least two reasons: (i) NaDCA has been reported to inhibit proliferation and to induce apoptosis in cells obtained from human colon cancer [48,49] and gastric carcinoma [50]; (ii) coupling with bile acid (such as deoxycholic acid) moieties has been suggested to be a promising strategy for liver-targeted drug delivery due to the presence of bile acid receptors on hepatocytes [51]. Deoxycholic acid modified conjugates have been developed and proposed as suitable novel carriers for anticancer drugs including epirubicin and paclitaxel [52,53].…”
Section: Biological Evaluationmentioning
confidence: 99%